Influence Of The Experiment-Geometry On The Attenuation Of Beta-Particles - Ameen, Sarbast S.; Ahmed, Ari K.; Abdulla, Rawand H. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The influence of the geometry has been investigated; experiments have been performed for qualitative determination of the effect of Experiment Geometry On beta-ray absorption coefficient. It has been demonstrated that the reduction in the number of beta-particles transmitted through absorbers is due mainly to the process of deflection from initial direction. The investigations have been performed using the beta radioactive source Sr( Y) 39 90 38 90, and scintillation detector with stilbene crystal. An emperical relation for the number of beta-particles transmitted through an absorber, which accounts for the geometry and the contribution of scattered electron has been tested.
Keywords: betaradiation; absorption coefficient; betascattering; attenuation coefficient; betaspectrum